Laryngopharyngeale Refluxerkrankung (LPRD) bei Kindern - Reichel, Oliver; Saravakos, Panagiotis; Lorenz, Kai J. (Laryngo-Rhino-Otologie, 2017)
Zwischen 5 und 20 % aller Kinder leiden an einer gastroösophagealen Refluxerkrankung (GERD), die zu Erosionen, Ulzera und Metaplasien der Ösophagusschleimhaut führen kann. Überwindet der Mageninhalt in pathologischer Häufigkeit und Intensität auch den kindlichen oberen Ösophagussphinkter, liegt eine laryngopharyngeale Refluxerkrankung (LPRD) vor. Die mit einer kindlichen LPRD assoziierten Symptome und Folgeerkrankungen sind äußerst vielfältig.LPRD in children is characterized by symptoms, clinical findings, and sequelae caused by the reflux of gastric acid, bile acid or refluxate containing pepsin beyond the esophagus. For diagnostic procedures and therapy of gastroesophageal reflux disease (GERD) in children and adults widely accepted guidelines have been established. However, diagnosis and therapy of LPRD in children remains a continuous issue of inter- and intradisciplinary discussions. Although both GERD and LPRD in children are reflux-induced diseases, these two entities are different in symptoms, cause, diagnostic procedures, and therapy. Thus, the terms GERD and LPRD are not eligible to be used as synonyms.Otorhinolaryngologists are becoming more and more involved in the management of children with suspicious LPRD. With flexible transnasal laryngopharyngoscopy being one of the most important diagnostic tools for LPRD detection, otorhinolaryngologists play an important role in the interdisciplinary diagnostic network of physicians treating children with suspected LPRD. The present article highlights age-dependent clinical symptoms, diagnostic tools, differential diagnoses, and adequate therapy for pediatric LPRD.
Keywords: Hals-Nasen-Ohren-Heilkunde; Reflux; laryngopharyngeale Refluxerkrankung; Magensaft; Endoskopie; gastroösophageale Refluxerkrankung